2013
DOI: 10.1016/j.jsb.2013.02.011
|View full text |Cite
|
Sign up to set email alerts
|

Role of trimer–trimer interaction of bacteriorhodopsin studied by optical spectroscopy and high-speed atomic force microscopy

Abstract: Bacteriorhodopsin (bR) trimers form a two-dimensional hexagonal lattice in the purple membrane of Halobacterium salinarum. However, the physiological significance of forming the lattice has long been elusive. Here, we study this issue by comparing properties of assembled and non-assembled bR trimers using directed mutagenesis, high-speed atomic force microscopy (HS-AFM), optical spectroscopy, and a proton pumping assay. First, we show that the bonds formed between W12 and F135 amino acid residues are responsib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
42
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 41 publications
2
42
0
Order By: Relevance
“…16−24 For BR and HR, it has been shown that some amino acids on the interprotomer interaction surface contribute to the trimer formation and that inter-and intratrimer interactions are crucial for maintaining appropriate photoreactions. 22,25 A nonmarine eubacterial proton pump, Gloeobacter rhodopsin (GR), forms a trimer as well as BR and HR, 26 however, its molecular mechanism is different from BR and HR because the sign of the visible CD spectrum of GR is opposite from those of BR and HR ( Figure 1C). 20,22,27,28 The trimeric assembly of GR is maintained by an His87−Asp121 salt bridge, which is completely conserved among the eubacterial proton pumps.…”
Section: ■ Introductionmentioning
confidence: 99%
“…16−24 For BR and HR, it has been shown that some amino acids on the interprotomer interaction surface contribute to the trimer formation and that inter-and intratrimer interactions are crucial for maintaining appropriate photoreactions. 22,25 A nonmarine eubacterial proton pump, Gloeobacter rhodopsin (GR), forms a trimer as well as BR and HR, 26 however, its molecular mechanism is different from BR and HR because the sign of the visible CD spectrum of GR is opposite from those of BR and HR ( Figure 1C). 20,22,27,28 The trimeric assembly of GR is maintained by an His87−Asp121 salt bridge, which is completely conserved among the eubacterial proton pumps.…”
Section: ■ Introductionmentioning
confidence: 99%
“…From this observation, it was revealed that this inter-trimer bR-bR contact engenders both positive and (Ruan et al 2017) Height change in MloK1 cyclic nucleotide-modulated channels (Kowal et al 2014;Rangl et al 2016) Spiral spring formation by ESCRT protein (Chiaruttini et al 2015) Stiffness map of membrane protein moieties estimated from thermal motion (Preiner et al 2015) Diffusion and interaction of outer membrane protein F (OmpF) (Casuso et al 2012) Bacteriorhodopsin responding to light Yamashita et al 2013) ATP-induced height change of Ca 2+ pump (Yokokawa and Takeyasu Moving net-like structure formed by prion covering living bacterial surface (Yamashita et al 2012;Oestreicher et al 2015) Dynamic morphological changes in living cells (Shibata et al 2015) Dynamics of nucleoporins inside nuclear porin complexes of Xenopus laevis oocytes (Sakiyama et al 2016) Responses of bacteria to antimicrobial peptide (Fantner et al 2010) a Personal communications negative cooperative effects in the decay kinetics as the initial bR recovers. Further HS-AFM studies of bR successfully revealed how bR molecules form trimers and why the trimer formation is required for the function of bR (Yamashita et al 2013).…”
Section: Hs-afm Imaging Of Biological Molecules In Actionmentioning
confidence: 99%
“…The high-resolution imaging of surface macromolecules has remained elusive due to the limited speed of standard AFM imaging. However, the recent development of high-speed AFM (HS-AFM) has enabled the resolution of such structures primarily due to HS-AFMs to show exceptional temporal resolution (>100 ms) and significantly reduced scanning forces [33][34][35].…”
Section: High-speed Afmmentioning
confidence: 99%
“…In one such series of studies, the dynamics of conformational changes of bacteriorhodopsin (bR) was successfully imaged in response to electrochemical radiation stimulation [33,36,37]. During initial studies, the group observed conformational changes in the form of a 0.69 ± 0.15 nm displacement of the center mass of the trimer structure when exposed to green light.…”
Section: High-speed Afmmentioning
confidence: 99%
See 1 more Smart Citation